Oxidative stress, advanced glycation end products and residual renal function in the rat model of unilateral ureteral obstruction: effects of phlogenzym and losartan - Sebekova, K.Jr.; Blazicek, Jr.P.; Syrova, D.; Galbavy, S.; Schinzel, R.; Heidland, A.; Sebekova, K. (Вiopolymers and Cell, 2010)
Aim. Oxidative stress plays a role in the pathogenesis of ureteral obstruction. Methods. We studied parameters of oxidative status, levels of advanced glycation end products (AGEs), and contralateral (CL) kidney function in the rat model of unilateral ureteral obstruction (UUO). The effect of Phlogenzym (12 mg/day orally); losartan (20 mg/l in drinking water), and their combination was studied. Results. In placebo-administered UUO rats AGEs and malondialdehyde levels were higher than in the sham operated controls. Function of the CL kidney was slightly impaired, its collagen content and protein/deoxyribonucleic acid ratio (P/DNA) in the glomeruli increased. All treatments prevented the rise in collagen content, P/DNA ratio, and improved CL kidney function. Phlogenzym ameliorated lipid peroxidation and AGE levels. Conclusions. In the model of UUO systemically increased oxidative stress may play a role in development of tubulointerstitial fibrosis and in the functional impairment of the CL kidney. Suppression of the oxidative stress and blockade of angiotensin-1 receptors might mitigate the progression of obstructive uropathy.